Video-article publication as strategy to enhance science consumption - Santos, Adriana Barbosa [UNESP] (FapUNIFESP (SciELO), 2022)
New technologies have promoted important changes in the social relations in recent years, stimulating the growth of scientific content production in audiovisual format, especially of video-articles. This article examines the applicability of the new trends of audiovisual publications as a strategy to enhance science consumption inside as well as outside the academic ecosystem. An exploratory-descriptive survey was performed with Brazilian researchers from the Health Sciences and Human Sciences areas, focusing on mitigating the lack of empirical evidence, regarding four points: their view of science consumption in Brazil; the lack of knowledge on the video-articles like scientific communication; the level of interest in scientific publications in audiovisual format; and feelings about the visibility and recognition of science in Brazil. Results reinforce the interest in audiovisual resource usage in scientific communication valorization, given that the researchers are interested in video-articles publishing for improving visibility, altmetrics, and expanding the dissemination of scientific culture, focusing to enhance science consumption.
Publicação de videoartigos como estratégia para impulsionar o consumo de Ciência
Keywords: Audiovisual communication; Audiovisual materials; Scholar activity; Scholars communication; Scientific knowledge